FREQUENCY OF SPUTUM POSITIVE AFB CASES AMONG PATIENTS OF PULMONARY TUBERCULOSIS IN TERTIARY CARE HOSPITALS OF NORTHERN PAKISTAN - Khattak, Mohammad Ishaq; ullah, Ihsan; Muhammad, Amir; Khan, Nisar; Zaman, Munawar (Journal of Ayub Medical College Abbottabad, 2010)
Objective: This study was aimed to find out the frequency of sputum positive Acid Fast Bacilli (AFB) cases among pulmonary tuberculosis patients and to determine those patients who are the potential source of transmitting infection. Methods: This study was conducted in four medical units of Khyber Teaching Hospital, Peshawar and Chest Unit, Ayub Teaching Hospital, Abbottabad in collaboration with the pathology unit of Khyber Teaching Hospital, Peshawar, and Kohat Institute of Medical Sciences, Kohat. Three specimens of sputum were collected for three consecutive days in the morning and were transported immediately to the laboratory along with full details of the patients. Results: Out of two hundred total patients studied, 104 patients (52%) were sputum AFB positive. Among the 104 patients 60 patients (57.4%) were females. Sixty-four (61.52%) individuals were between 20-50 years. Majority of the patients were from poor, deprived and lower social class. Fifty-two (50%) patients had monthly income of less than Rs. 4,000; only 8 patients (7.67%) had monthly income of more than Rs. 12,000). Forty-eight patients <46.12% were house wives, 10 patients (9.61%) were unemployed. Most of the patients were under weight for their age and height. 24 patients (23.06%) were below 42 kg. The maximum (53.84%) number of patients was in weight range of 43-50 kg. Conclusion: Sputum AFB positive pulmonary tuberculosis is more in individuals of low socioeconomic group and in females. The patients put their children and family members at risk of tuberculosis infection. For the control of this disease early diagnosis of active disease and their treatment under supervision is important. Keyword: Sputum, AFB-Positive, Pulmonary tuberculosis, Low socioeconomic group